Implementation of Data Mining Using Simple Linear Regression Algorithm to Predict Export Values - Aldi Bastiatul Fawait; Sitti Rahmah; Apolonia Diana Sherly da Costa; Nazaruddin Insyroh; Asno Azzawagama Firdaus (PT. Teknologi Futuristik Indonesia, 2025)
This study aims to analyze the trends in export value in East Kalimantan. The research utilizes secondary data sourced directly from the Central Statistics Agency of East Kalimantan Province. A simple linear regression algorithm for data mining is employed as the analytical method. The findings indicate a decline in East Kalimantan's export value from January 2022 to April 2024, as well as in the forecasted export value from May 2024 to December 2024. The prediction model achieved a Root Mean Square Error (RMSE) value of 3.182%, demonstrating a high level of accuracy in estimating export values. This research is expected to serve as a valuable reference for stakeholders in formulating strategies to enhance East Kalimantan's export performance and contribute to the region's future economic development.